2012
DOI: 10.1016/j.physbeh.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and physiological correlates of impulsivity in the domestic dog (Canis familiaris)

Abstract: Impulsivity is a trait related to inhibitory control which is expressed in a range of behaviours. Impulsive individuals show a decreased ability to tolerate delay of reinforcement, and more impulsive behaviour has been linked to decreased levels of serotonin and dopamine in a number of species. In domestic dogs, impulsivity is implicated in problem behaviours that result from a lack of self control, but currently there are no published studies that assess behavioural and physiological measures of impulsivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 53 publications
(52 reference statements)
4
95
3
5
Order By: Relevance
“…Moreover, a different study reported that high impulsivity is linked to lower levels of serotonin and dopamine in dogs, a phenomenon which has previously been reported in humans (Wright et al 2012). In light of our findings of behavioral differences across contexts, it would be instructive to see whether the neurobiological data also reflect differences in depletion and chemical levels depending upon context.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, a different study reported that high impulsivity is linked to lower levels of serotonin and dopamine in dogs, a phenomenon which has previously been reported in humans (Wright et al 2012). In light of our findings of behavioral differences across contexts, it would be instructive to see whether the neurobiological data also reflect differences in depletion and chemical levels depending upon context.…”
Section: Discussionsupporting
confidence: 55%
“…The term does not imply a diagnosis of pathological hyperactivity associated with impaired attention as in humans beings (Blum and others 2008, Wright and others 2012), and a lower level of activity might also be related to a lower motivation to play and seeking rewards in general.…”
Section: Discussionmentioning
confidence: 99%
“…Delay discounting procedures have also been studied using other non-human animals such as pigeons, rhesus monkeys, chimpanzees and bonobos (for review see Vanderveldt, Oliveira, & Green, 2016), and dogs (e.g. Wright, Mills, & Pollux, 2012) with response types such as pecking response keys, pressing response levers, and depressing wooden panels, respectively. There is a large literature concerning differences in delay discounting across mice and rats due to genetic variations (for review of both human and animal literature see MacKillop, 2013), and drug exposure (for review see Setlow, Mendez, Mitchell, & Simon, 2009).…”
Section: Impulsive Behavior: Definition and Measurementmentioning
confidence: 99%